The impact of outsourcing on performance and competitive priorities among Malaysian SMEs - Halim, H. A. (IGI Global, 2016)
The objective of this research is to examine the influence of outsourcing on financial performance andcompetitive priories of Malaysian SMEs. A data sample of 100 SMEs was analyzed to examine theserelationships. The analysis was conducted via Partial Least Squares. Based on the findings, while outsourcinghas significant influence of SMEs financial performance in Malaysian context, outsourcingactivities do not have an impact on competitive priorities. Outsourcing approach emphasizing on theestablishment of core competitive advantage, allows Malaysian SMEs to get the numerous benefits suchas overall sales growth, market share, net profit, return on investment, and financial liquidity.